Novel methods of Fusarium toxins’ production for toxicological experiments - Fodor, Judit; Németh, M.; Kametler, Laszló; Pósa, Roland; Kovács, Melinda; Horn, Péter (Acta Agraria Kaposváriensis, 2006)
Studies were performed to develop a novel, efficient and cost-effective method for fumonisin and T-2 toxin production, respectively, in sufficient quantities for animal toxicological experiments. On the basis of three earlier published fumonisin toxin production methods a novel method was developed. Three, absolutely necessary factors were taken into account and tested in a serial experiment. The Fusarium verticillioides strain MRC 826 was directly inoculated onto soaked, autoclaved, whole maize kernels (50 g/1.7 l jar). The inoculation was performed by standard spore suspension (1·106 /ml), a 5/2 surface/volume culture was prepared and incubated at 25 °C for 5 weeks. To maintain the optimal aw of approximately 1.00, the evaporated water was re-filled weekly. A final concentration of 4454 ± 1060.9 mg kg-1 fumonisin B1 was reached. T-2 toxin was produced experimentally on ground maize by Fusarium sporotrichioides strain NRRL 3299. With the method in this study similarly high T-2 toxin concentration can be reached as in case of fumonisin production. In the laboratory practice, applying the above settings, a high toxin production can be obtained.
Keywords: fumonisin B1; T-2 toxin; production methods